Permanent magnet synchronous machines flux linkage estimation with zero steady‐state error and its field‐programmable gate array implementation. Issue 4 (1st April 2015) - Zanuso, Giovanni; Peretti, Luca; Zigliotto, Mauro
Abstract : The paper analyses a combined current model–voltage model estimator for flux linkages in permanent magnet synchronous machines, with the capability of converging to exact flux estimation even in presence of mismatches because of magnetic saturation. As a trend in next‐generation electric drives, the whole algorithm, including both the flux estimator and the standard field‐oriented control, has been implemented in a field‐programmable gate array (FPGA) chip. Simulations and experimental tests, along with some figures for the FPGA selection, have been included in the study.